Find the Slope and Y-Intercept (-6,-1) , (-9,6)

Math
(-6,-1) , (-9,6)
Find the value of the slope.
Tap for more steps…
Slope is equal to the change in y over the change in x, or rise over run.
m=change in ychange in x
The change in x is equal to the difference in x-coordinates (also called run), and the change in y is equal to the difference in y-coordinates (also called rise).
m=y2-y1x2-x1
Substitute in the values of x and y into the equation to find the slope.
m=6-(-1)-9-(-6)
Simplify.
Tap for more steps…
Simplify the numerator.
Tap for more steps…
Multiply -1 by -1.
m=6+1-9-(-6)
Add 6 and 1.
m=7-9-(-6)
m=7-9-(-6)
Simplify the denominator.
Tap for more steps…
Multiply -1 by -6.
m=7-9+6
Add -9 and 6.
m=7-3
m=7-3
Move the negative in front of the fraction.
m=-73
m=-73
m=-73
Find the value of the y-intercept.
Tap for more steps…
Substitute the value of m into the slope-intercept form of the equation, y=mx+b.
y=(-73)⋅x+b
Substitute the value of x into the slope-intercept form of the equation, y=mx+b.
y=(-73)⋅(-6)+b
Substitute the value of y into the slope-intercept form of the equation, y=mx+b.
-1=(-73)⋅(-6)+b
Rewrite the equation as (-73)⋅(-6)+b=-1.
(-73)⋅(-6)+b=-1
Simplify each term.
Tap for more steps…
Cancel the common factor of 3.
Tap for more steps…
Move the leading negative in -73 into the numerator.
-73⋅-6+b=-1
Factor 3 out of -6.
-73⋅(3(-2))+b=-1
Cancel the common factor.
-73⋅(3⋅-2)+b=-1
Rewrite the expression.
-7⋅-2+b=-1
-7⋅-2+b=-1
Multiply -7 by -2.
14+b=-1
14+b=-1
Move all terms not containing b to the right side of the equation.
Tap for more steps…
Subtract 14 from both sides of the equation.
b=-1-14
Subtract 14 from -1.
b=-15
b=-15
b=-15
The values of the slope and y-intercept are m=-73 and b=-15.
m=-73
b=-15
Find the Slope and Y-Intercept (-6,-1) , (-9,6)

Download our
App from the store

Create a High Performed UI/UX Design from a Silicon Valley.

Scroll to top